Equity premium prediction: Are economic and technical indicators instable? - Fabian Baetje; Lukas Menkhoff (Kiel Institute for the World Economy (IfW), 2015)
We show that technical indicators deliver economic value in predicting the U.S. equity premium. A crucial element of this value stems from the stability of return predictability over the full sample period from 1950 to 2013. Results tentatively improve over time and beat alternatives over sub-periods. By contrast, economic indicators work well only until the 1970s, thereafter they lose predictive power, even when the last crisis is considered. Translating the predictive power of technical indicators into a standard investment strategy delivers an average Sharpe Ratio of 0.6 p.a. for investors who had entered the market at any point in time.
Keywords: G17; G12; 330; equity premium predictability; economic indicators; technical indicators; break tests